Factors influences rising in household debt level among customers at Bank Rakyat, Putrajaya / Nurfadilah Ahamad Bakry - Ahamad Bakry, Nurfadilah (Faculty of Business and Management, 2015)
The purpose of this research is to determine “Factors Influences Rising in Household Debt Level Among Customers at Bank Rakyat, Putrajaya”. Household debt is one of the important factors that need to be done carefully. This is because an error in managing household debt will only lead to financial distress and can lead to bankruptcy. Thus, this paper will essentially close to find out the factors influences household debt rising. The objectives of this research is to investigate the relationships between income inequalities, house prices and loose credit condition with the rising of household debt level and to identify the most important factors that influences the rising of household debt level. Besides that, this research is a quantitative research study whereby the findings of the study are analyzed by using the Statistical Package for the Social Sciences (SPSS). Next, the data collected in this research is analyzed by using reliability test, descriptive analysis, correlation analysis and regression analysis in order to achieve the research objectives. In order to obtain the findings, a set of questionnaire consists of 5 sections is distributed to 200 respondents. Result shows income inequalities have been most influence factors towards rising in household debt level among customers at Bank Rakyat, Putrajaya. There is also recommendation in this research which to emphasize rising in household debt level especially among public and private sectors in Malaysia.